Tinjauan Yuridis Terhadap Pertimbangan Hukum Oleh Hakim Dalam Putusan Perkara Nomor: 669/PID.SUS/2014/ PN.BLB Dihubungkan Dengan Pasal 55 Undang-Undang Nomor 22 Tahun 2001 Tentang Minyak dan Gas Bumi - Yusup Juhara (Universitas Islam Nusantara, 2018)
Oil and natural gas are natural resources that are controlled by the State and have an important role in the national economy so that their management needs to be carried out optimally. In an effort to create oil and gas business activities in order to realize the increase in prosperity and welfare of the people, Law Number 22 Year 2001 concerning Oil and Natural Gas has been established. In the implementation of the business of supplying and distributing subsidized fuels, there is often fraud in the effort to distribute BBM in the regions, resulting in a fairly high price difference between industrial fuels and subsidized fuels which opens the opportunity for various parties to commit irregularities or without permission. Just as there are criminal acts that have been decided by the Bale Bandung District Court with Case Number: 669 / Pid. Sus / 2014 / PN.Blb. Based on these problems, the authors identify the following problems: 1) What is the legal consideration by the judge in making a decision in Case umber: 669 / Pid.Sus / 2014 / PN.Blb; 2) How is the application of criminal law against criminal acts of transportation, storage and trade of fuel oil that is subsidized without permission based on Article 55 of Law Number 22 Year 2001 concerning Oil and Natural Gas.